Mycotoxin producers in the Aspergillus genus : an update - Varga, János; Baranyi, Nikolett; Chandrasekaran, Muthusamy; Vágvölgyi, Csaba; Kocsubé, Sándor (Acta Biologica Szegediensis, 2015)
Mycotoxins are secondary metabolites of fungi. Species assigned to the Aspergillus genus produce a wide range of mycotoxins which can contaminate several agricultural products, and cause various human and animal diseases. In this review, we wish to give an overview of producers of Aspergillus mycotoxins in view of recent scientific data.